SYNTHETIC APERTURE RADAR FOR ASSESSING LAND DEGRADATION IN A SALT MINING AREA – OCNELE MARI CASE-STUDY - VIOLETA POENARU; ALEXANDRU BADEA; SORIN MIHAI CÎMPEANU; IULIA DANA NEGULA (Revue Roumaine de Géographie)
Human activities through anthropogenic changes had negative impacts not only on land cover, but on many aspects of local, regional and global environments, including climate, biodiversity, soil condition and sediment flow. Remote sensing imagery with its useful qualitative and quantitative observations acquired repetitively and with large spatial coverage, offers opportunity for early detection and warning of land degradation risk. This paper investigates the Synthetic Aperture Radar techniques potential to assess land degradation in a salt mining area affected by subsidence phenomena. Based on backscattering temporal variability of SAR data and coherence, we propose to analyze a multi-temporal RADARSAT2 data acquired in interferometric mode by applying SAR interferometry, SAR polarimetry and SAR change detection approaches.